Virtual CMM-based model for uncertainty estimation of coordinate measurements performed in industrial conditions. (February 2017) - Gąska, A.; Harmatys, W.; Gąska, P.; Gruza, M.; Gromczak, K.; Ostrowska, K.
Graphical abstract: Highlights: The general procedure of Virtual CMM implementation in industrial conditions was developed. The implementation experiments were shortened about 4 times comparing to typical Virtual CMM models. Verification tests proved correct functioning of model in temperature ranging from 18 to 22 °C. Abstract: Due to the rigorous requirements for implementation of virtual models of CMMs, such models are primarily used in high-profile calibration laboratories. This paper presents a novel methodology for implementing a Virtual CMM model capable of correct uncertainty determination for measurements performed in less stable, industrial conditions. Verification results obtained under varying ambient conditions are also presented to prove the correctness of proposed methodology.